Caracterização morfofuncional das brânquias de Arapaima gigas, durante a transição da respiração aquática para respiração aérea - Ramos, Cleverson Agner (2008)
The gill structure of the Amazon fish Arapaima gigas, an obligatory air breather, was analyzed during its transition to obligatory air breathing behavior and the obtained data was related to its breathing mode. Gills of fish weighing between 2 to 5000g were collected, fixed and processed for morphometric analysis, histochemistry, imunohistochemistry, transmission (TEM) and scanning (SEM) electron microscopy (chloride cell fractional area, CCFA and density). In the first stages of development the gill filaments is as those of water-breathers, but there s intense changes while the animal grow, with influence on respiratory function and ionic exchanges. The lamellae keeps its organizational structure, including red cells passing through it, but them become to vestigial in fish since 1000g, being the interlamellar regions filled with filament cells. The most important cell types of the gill epithelia are the chloride cells (CCs), mucous cells (MCs) and the pavement cells (PCs). The PCs shows irregular shape and random microridges on the cell surface. Two cell processes are involved to gill changes, cells proliferation and programmed death cells (apoptosis); there is an intense proliferating cells until animals reach 500-600g. Apoptotics cells were low in all the animals observed. The number of CCs are low in animals under 100-200g and increased in the filament and lamellar epithelia in animals up to 1000g as well as the CCFA. Two kinds of MCs were observed, PAS positive and Alcian Blue positive. There was a significant raise in both cells until animals with 100-200g and PAS positives until 500-600g. These cells seem to play an important role relation with ion regulation. The transition to air breathing and the restriction for aquatic respiration result in gill changes in A. gigas, and the gills may play other important functions like ion and acid-base regulation, optimized by its epithelia cell kinds and its design.